Histological typing of endocrine tumours - Solcia, Enrico; Klöppel, Günter; Sobin, L. H (Springer, 2000)
The second edition of this book updates the \"WHO Classification of Endocrine Tumours\" proposed in 1980 and incorporates many new tumour entities and pertinent concepts that have developed since that time. It is the result of a collaborative effort of 9 pathologists from different countries, in addition to informal contributions and discussions by many other colleagues. Efforts have been especially made to integrate into the fundamental backbone of the histologic classification a number of prognostic and functional parameters now essential for appropriate diagnosis and clinicopathologic evaluation of endocrine tumours.
International histological classification of tumours, ISSN 0538-7736
Keywords: Endocrine Gland Neoplasms; nádory endokrinních žláz; onkologie; endokrinologie